The Evaluasi Implementasi Kebijakan Pembentukan Tim Tanggap Insiden Siber pada Sektor Pemerintah - Prabaswari; Muhamad Alfikri; Irdam Ahmad (Research and Development Agency Ministry of Home Affairs, 2022)
Since the COVID-19 pandemic hit the world, all daily activities have transformed. People’s online activities for work, study, transactions, and socializing have increased significantly. This phenomenon increases cybercrime, targeting but not limited to government-owned systems. The National Cyber and Crypto Agency (BSSN) issued Regulation No. 10 of 2020, the Cyber Security Incident Response Team (CSIRT), to address this issue.. Of course, establishing a solid and competent CSIRT in every government agency is required to realize cybersecurity resilience, particularly in the government sector. This research aims to explain the BSSN policy regarding the CSIRT team and explore its implementation strategy. With descriptive-explanatory research methods, the theory used is public policy and implementation strategy. According to the findings of this study, agencies that already have a CSIRT experience fewer cyber incidents and recover more quickly from a cyber-attack.